EFEKTIFITAS SISTEM TEMU KEMBALI INFORMASI DALAM MENINGKATKAN PEMANFAATAN KOLEKSI PADA PERPUSTAKAAN STMIK POTENSI UTAMA MEDAN - Muhammad Yafizham Alwi (Jurnal Pustaka Nusantara dan Budaya, 2013)
The purpose of this study was to determine the effectiveness of the retrieval system of information in improving utilization library collections by student at the Library STMIK Potensi Utama Medan. This study is descriptive survey research method by distributing questionnaires. The study population is students who are members of the library located at STMIK Potensi Utama numbered 2560 people. Sampling techniques using proportionate stratified random sampling technique to obtain a sample of 256 students consisting of three departments, namely: information systems, management informatics and informatics techniques. The results show that the retrieval systems use low 1 time (65.5%). In addition, only (47.7%) use a collection of library materials, so that this condition results in lower effectiveness of information retrieval in the use of library materials in the library collection STMIK Potensi Utama Medan. Keywords: Using retrieval system of information , Utilization Collection.